Visualizing and Visualizing Representations. Issue 3 (1st August 2018) - MATRAVERS, DEREK
ABSTRACT: Opponents of "the dependency thesis" (the view that when we visualize an F what we do is imagine seeing an F) have used an analogy between visualizing and viewing visual representations to bolster their skepticism. This article explores this analogy and argues that when we set out to visualize an F, sometimes what we visualize is either (1) influenced by our prior exposure to visual representations of an F or (2) best described as a visual representation of an F. The ramifications of this are explored, both in the light of arguments over the dependency thesis, and also in the light of the surprising data that suggest that at least during the 1940s and 1950s, people dreamed in black and white.